2022
DOI: 10.5005/jp-journals-10016-1290
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endocrine and Metabolic Profile of Obese and Lean PCOS Women with Infertility

Abstract: ReseaRch aRticlecauses of HA, primary hypothalamic amenorrhea, primary ovarian failure, thyroid disease, and prolactin disorder were excluded. The study was ethically conducted in accordance with the Declaration of Helsinki. Ethical approval was obtained prior to the commencement of the study (90th ECM/II B-Thesis/P36).The women enrolled underwent an assessment of height, weight, and BMI. Women were classified into two groups according to BMI group I with BMI <23 kg/m 2 (lean and underweight) and group II with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Agarwal at el and Akshaya et al studies also had raised WHR in obese PCOS women. 5,14 It was noted that central obesity is more common in obese PCOS than the lean PCOS woman which is comparable to present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Agarwal at el and Akshaya et al studies also had raised WHR in obese PCOS women. 5,14 It was noted that central obesity is more common in obese PCOS than the lean PCOS woman which is comparable to present study.…”
Section: Discussionsupporting
confidence: 91%
“…A study by Agarwal et al and Saxena et al did not find any difference between BMI and LH/FSH ratio in women with PCOS. 14,15 In this study, we found no significant difference in the frequency of serum TSH between the two groups; Saxena et al also found comparable findings. 15 As opposed to nonobese women with PCOS, Liou et al reported that obese women with PCOS had lower blood LH levels and a lower LH to FSH ratio.…”
Section: Discussionsupporting
confidence: 53%
“…Similar studies by Gupta et al . [ 17 ] and Kar[ 18 ] have shown higher triglyceride values in the obese when compared with the lean women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] In another study, the number of women with low HDL was equally distributed between both the groups. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%